Efektivitas Self Efficacy terhadap Pemahaman Tanda Bahaya Kehamilan menggunakan Video dan Buku Kesehatan Ibu dan Anak - Herinawati Herinawati; Neni Heryani; Susanti Susanti; Atika Fadhilah Danaz Nst; Imelda Imelda; Iksaruddin Iksaruddin (Universitas Baiturrahim, 2021)
One effort to increase the understanding of pregnant women about the danger signs of pregnancy is to carry out social persuasion in the form of education to improve self-efficacy of understanding the danger signs. Education can be done using a variety of media, namely visual media, audio and audio visual. This literature study aims to find out Effectiveness of Self-Efficacy towards Understanding of Pregnancy Danger Signs using Videos and Books of MCH.The design used in this study is the study of literature. The type of data used is secondary data obtained from journal database searches taken through the internet, both national and international journals. The search results obtained as many as 12 journals that are considered in accordance with the purpose of the study. The results of the literature study show that there is an effect of Self-Efficacy on Understanding of the Signs of danger of pregnancy using Video, there is an effect of Self-Efficacy of Understanding of Signs of danger of pregnancy using the MCH Handbook, and Video media is more effective than the Book of MCH. The conclusion of this literature study is The effectiveness of education delivered is affected by a variety of things, one of which is the media used. The better the media used, the easier the reception of material by respondents. Recommendations from this literature study virtue need to improve the health promotion strategy by advocacy strategy, social support strategy and community empowerment strategy